PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN DENGAN MENGGUNAKAN STRATEGI BIMBINGAN LANGSUNG PADA SISWA KELAS II SD INPRES OEBESA - Yunaria Faot; Konradus Silvester Jenahut S.Pd.,M.Pd; Angelina C.O.R Lake, S.Pd.,M.Pd (STKIP Subang, 2026)
Enhancing Early Reading Skills Using the Direct Instruction Strategy in Second Grade Students of SD Inpres Oebesa. Undergraduate Thesis, Faculty of Teacher Training and Education, San Pedro University, October 2025.This study aims to improve the early reading skills of second-grade students at SD Inpres Oebesa through the application of the direct instruction strategy. This research employs a classroom action research (CAR) design, which was carried out in two cycles. Each cycle consisted of four stages: planning, action implementation, observation, and reflection. The subjects of this study were 15 second-grade students of SD Inpres Oebesa. Data were collected through observation, reading skill tests, and documentation. The collected data were analyzed descriptively using both qualitative and quantitative approaches. The results of the study showed that the application of the direct instruction strategy was effective in improving students’ early reading skills. In the first cycle, the average reading skill score was 68, categorized as “fair,” while in the second cycle, it increased to 85, categorized as “good.” In addition, students appeared more active and motivated during reading activities. Therefore, it can be concluded that the use of the direct instruction strategy is effective in improving the early reading skills of second-grade students at SD Inpres Oebesa.